2008
DOI: 10.1007/s11270-008-9727-7
|View full text |Cite
|
Sign up to set email alerts
|

Competition from Cu(II), Zn(II) and Cd(II) in Pb(II) Binding to Suwannee River Fulvic Acid

Abstract: This is a study of trace metal competition in the complexation of Pb(II) by well-characterized humic substances, namely Suwannee River Fulvic Acid (SRFA) in model solutions. It was found that Cu (II) seems to compete with Pb

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 26 publications
1
15
1
Order By: Relevance
“…5) show in all cases the release of more than 62% of sorbed Zn (mean 82%), and hence that Zn sorption is much more reversible in these and similar soils than that of Cu , Hg (Yin et al, 1997) or Pb (Strawn and Sparks, 2000). The reversibility of Zn sorption is in keeping with previous reports (Shi et al, 2008), and is attributed to most sorbed Zn being weakly bound to soil constituents (Diesing et al, 2008) and its low affinity for organic matter (Hernández et al, 2007;Chakraborty and Chakrabarti, 2008), for which Cu, Hg and Pb all have high affinity (Olsson et al, 2007;Bai et al, 2008;Chakraborty and Chakrabarti, 2008). Table 4 lists the results of fitting the desorption data with the first order equation…”
Section: Desorption Of Znsupporting
confidence: 83%
See 1 more Smart Citation
“…5) show in all cases the release of more than 62% of sorbed Zn (mean 82%), and hence that Zn sorption is much more reversible in these and similar soils than that of Cu , Hg (Yin et al, 1997) or Pb (Strawn and Sparks, 2000). The reversibility of Zn sorption is in keeping with previous reports (Shi et al, 2008), and is attributed to most sorbed Zn being weakly bound to soil constituents (Diesing et al, 2008) and its low affinity for organic matter (Hernández et al, 2007;Chakraborty and Chakrabarti, 2008), for which Cu, Hg and Pb all have high affinity (Olsson et al, 2007;Bai et al, 2008;Chakraborty and Chakrabarti, 2008). Table 4 lists the results of fitting the desorption data with the first order equation…”
Section: Desorption Of Znsupporting
confidence: 83%
“…Metal adsorption is highly affected by pH when oxides or hydroxides controlled metal retention. Moreover, Zn affinity for organic matter is much lower than other divalent metals (Hernández et al, 2007;Chakraborty and Chakrabarti, 2008), and therefore, it could be more vulnerable to pH changes.…”
Section: Competitive Sorption Of Zn and Cumentioning
confidence: 99%
“…The chemistry of trace metals and their interaction with natural ligands (such as, dissolved organic matter) are well studied in aquatic system as reflected by the large numbers of publications available in the literature (Achterberg and Braungardt, 1999;Bayen et al, 2006;Chakraborty, 2010;Chakraborty and Chakrabarti, 2008;Chakraborty et al, 2007;Chakraborty et al, 2009;Gopalapillai et al, 2008;Groschner and Appriou, 1994;Guthrie et al, 2005;Nicolau et al, 2008). However, the knowledge of speciation of trace metals and their interactions with heterogeneous binding sites present in sediments are not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…10 Studies have covered the AHS complexation with different metals under different pH conditions, ionic strength and concentration of metals and AHS. [11][12][13][14][15] A recent study demonstrated that solar radiation can also be an important factor in the complexation capacity of AHS with metals. 8,16 These authors showed that radiation alters the complexation capacity that the AHS had when not exposed to radiation previously.…”
Section: Introductionmentioning
confidence: 99%